Controversial issues in the management of older adults with early breast cancer - Mislang, Anna Rachelle; Cheung, Kwok-Leung; Hamaker, Marije E.; Kunkler, Ian; Markopoulos, Christos; Orecchia, Roberto; Brain, Etienne; Biganzoli, Laura (Elsevier, 2017)
It is well recognized that the incidence of breast cancer increases significantly with age. Despite this, older people remain under-represented in many clinical trials and their management relies on extrapolation of data from younger patients. Providing an aggressive intervention can be challenging, particularly in less fit older patients where a conservative approach is commonly perceived to be more appropriate. The optimal management of this population is unknown and treatment decision should be personalized. This review article will discuss several controversial issues in managing older adults with early breast cancer in a multidisciplinary setting, including the role of surgical treatment of the axilla in clinically node negative disease, radiotherapy after breast conservation surgery in low-risk tumours, personalizing adjuvant systemic therapy, and geriatric assessments in breast cancer treatment decisions.